2022
DOI: 10.1210/clinem/dgac667
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs Respond to Denosumab Treatment After 2 Years in Postmenopausal Women With Osteoporosis—the MiDeTe study

Abstract: Context MicroRNAs (miRNAs) are short, single-stranded, non-coding RNAs which regulate gene expression. They originate from various tissues including bone and regulate different biological mechanisms including bone metabolism. Objective The aim of this project was to investigate circulating miRNAs as promising biomarkers for treatment monitoring in women with postmenopausal osteoporosis on denosumab (DMAB) therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…There is only preliminary information about osteoporosis therapy’s effects on miRNAs, due to which the magnitude of the response has yet to be discovered, for example, the effect of bisphosphonate therapy on miRNA in man. There is some evidence for changes in miR-33-3p and mir-133a in response to teriparatide, as well as increases in miR-26b-5p and miR-454-3p of 100% to 200%, 26 although no change was reported by others. 27 The need for more consistency in these studies is likely explained by the high variability in miRNA measurements and points to the need to have studies that are sufficiently powered.…”
Section: Discussionmentioning
confidence: 89%
“…There is only preliminary information about osteoporosis therapy’s effects on miRNAs, due to which the magnitude of the response has yet to be discovered, for example, the effect of bisphosphonate therapy on miRNA in man. There is some evidence for changes in miR-33-3p and mir-133a in response to teriparatide, as well as increases in miR-26b-5p and miR-454-3p of 100% to 200%, 26 although no change was reported by others. 27 The need for more consistency in these studies is likely explained by the high variability in miRNA measurements and points to the need to have studies that are sufficiently powered.…”
Section: Discussionmentioning
confidence: 89%
“…Studies revealed that circulating miRNAs could also serve as potential biomarkers for AMD detection (Urbańska et al, 2022;Elshelmani and Rani, 2023), as reported in other chronic diseases, such as cancer (El-Daly et al, 2023), osteoporosis (Messner et al, 2022), epilepsy (Xie et al, 2023), pulmonary hypertension (Düzgün et al, 2023), nephropathies (Sun et al, 2022), and hepatitis (Jiang et al, 2023). Furthermore, the significance of circulating miRNAs in numerous therapeutic areas makes them a promising asset for translational medicine applications (Pozniak et al, 2022).…”
Section: Macular Degenerationmentioning
confidence: 90%
“…Similarly, Messner et al analyzed miRNA from patients’ serum with osteoporosis treated with Denosumab. They selected three (miR-454-3p, miR-26b-5p, and miR-584-5p), which were defined by the authors as top biomarker candidates for osteoporosis [ 93 ].…”
Section: Microrna Clinical Application For Osteoporosismentioning
confidence: 99%